Hydrodynamic resistance of the friction plates with longitudinal mikroborizdkamy and thin elastic coating - Коробов, В.І.; Клешня, Н.О. (Proceedings of National Aviation University, 2008)
Weight measurements in a water tunnel have shown that there exist a range of parameters of longitudinally fine-ribbed surface such that turbulent friction in flow over the surface is less then that over a smooth flat plate of the same projected area. Damping coating made from the thin layer of an elastic material and have interior longitudinal ribs of rigidity (overturn riblets) is more effective than usual riblets.